The Influence of Lifestyle, Price Perception, and Product Quality on Mobile Phone Purchase Decision - Rahmatia, R.; Anwar, Suhardi M.; Halim, Ibrahim; Sari, Harmita (Manunggal Halim Jaya, 2026)
This study aims to determine the contribution of lifestyle, price perception, and product quality to purchasing Oppo mobile phones at the Mulia Cell Store, Palopo City, Indonesia. The study population includes all Oppo consumers at the store, with a sample of 30 respondents selected using purposive sampling techniques. This study uses a quantitative approach, with data collection techniques through observation, questionnaire distribution, and documentation. Data analysis was carried out using SPSS version 26. The results of the study indicate that, (1) lifestyle has a positive and significant effect on purchasing decisions, (2) product quality does not have a significant effect, (3) price perception has a significant positive effect on purchasing decisions, and (4) simultaneously, the three variables have a joint effect on purchasing decisions. This study provides a practical contribution for business actors, especially Mulia Cell Store owners, in developing marketing strategies adjusted to consumer lifestyles, price perceptions, and product quality to improve purchasing decisions.